2022
DOI: 10.30919/es8d757
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of the pyrolysis of propylene glycol

Abstract: A kinetic model was developed to predict product evolution during the thermal degradation of propylene glycol (PG) under N2 atmosphere. Main aldehydes that form from PG pyrolysis are formaldehyde (FA), acetaldehyde (AA), propanal (PA), acetone (Ace), glyoxal (GA) and methyglyoxal (MGA). Activation energies (Ea) of the proposed reaction pathways were determined experimentally under a range of temperatures via sequential parameter estimation and quasi-steady state approximation assumption. They were compared aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Comparisons with literature experimental studies about PG pyrolysis , highlight significant differences in the nature of reaction products. The present study suggests that the main PG dehydration pathway leads directly to acetone (as methyloxirane and propanal were not observed), whereas the data obtained by Laino et al suggests that PG dehydration leads to methyloxirane, which in turn isomerizes to propanal and acetone.…”
Section: Description Of the Obtained Experimental Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Comparisons with literature experimental studies about PG pyrolysis , highlight significant differences in the nature of reaction products. The present study suggests that the main PG dehydration pathway leads directly to acetone (as methyloxirane and propanal were not observed), whereas the data obtained by Laino et al suggests that PG dehydration leads to methyloxirane, which in turn isomerizes to propanal and acetone.…”
Section: Description Of the Obtained Experimental Resultsmentioning
confidence: 87%
“…The present study suggests that the main PG dehydration pathway leads directly to acetone (as methyloxirane and propanal were not observed), whereas the data obtained by Laino et al suggests that PG dehydration leads to methyloxirane, which in turn isomerizes to propanal and acetone. AlGemayel et al observed both acetone and propanal but not methyloxirane (because their analytical method was only specific to carbonyl species). Methyloxirane and propanal are common oxidation products that were easily detected in previous studies by our group, , and there is no reason for not detecting them in the present study if formed.…”
Section: Description Of the Obtained Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer nanocomposites are gaining enormous interest in various fields like electromagnetic interference shielding, solar thermal energy harvesting, pyrolysis, flame retardancy improvement, dielectric properties tuning, anticorrosive agent and catalysis . In catalysis, use of polymers as a capping agent for metal nanoparticles is gaining enormous interest since the polymers help by transforming the reaction system into a homogeneous one by dispersing the nanoparticles in the reaction media.…”
Section: Introductionmentioning
confidence: 99%
“…Rupasinghe et al established a room-temperature technology for the depolymerization of silicon-based polymers, elastomers, and resins with low catalytic amount of fluorine in a specific high expansion organic solvent . In this way, the recycling of silicone rubber with specific chemical solvent is not only complicated and has low efficiency but also requires specific catalysts, which causes secondary pollution. , In contrast, pyrolysis technology has a great potential to recycle silicone rubber, and its main products are pyrolysis gas, pyrolysis oil, and pyrolytic carbon black, in which gas and oil can be used as good fuel and pyrolytic carbon black can be used as filler and has potential economic value. As the pyrolysis temperature of silicone rubber is relatively high, recycling waste silicone rubber by pyrolysis is rarely reported . In fact, a catalyst or co-pyrolysis has been widely used in the pyrolysis cycle of plastics to influence the pyrolysis products to improve the pyrolysis rate or reduce the activation energy. …”
Section: Introductionmentioning
confidence: 99%